2014
DOI: 10.1155/2014/819053
|View full text |Cite
|
Sign up to set email alerts
|

Scropolioside B Inhibits IL-1βand Cytokines Expression through NF-κB and Inflammasome NLRP3 Pathways

Abstract: Chronic inflammation is associated with various chronic illnesses including immunity disorders, cancer, neurodegeneration, and vascular diseases. Iridoids are compounds with anti-inflammatory properties. However their anti-inflammatory mechanism remains unclear. Here, we report that scropolioside B, isolated from a Tibetan medicine (Scrophularia dentata Royle ex Benth.), blocked expressions of TNF, IL-1, and IL-32 through NF-κB pathway. Scropolioside B inhibited NF-κB activity in a dose-dependent manner with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Interestingly, the IL-1β mRNA level was significantly decreased not only during the period that the NF-κB level increased but also when the level of NF-κB began to decrease at 90 days. Similarly, Zhu et al have observed an increase in the transcription of NF-κB and an association between the increased NF-κB expression and an increased level of IL-1β [23]. Thus, these results show the persistence of the effect of NF-κB on IL-1β [24,25].…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, the IL-1β mRNA level was significantly decreased not only during the period that the NF-κB level increased but also when the level of NF-κB began to decrease at 90 days. Similarly, Zhu et al have observed an increase in the transcription of NF-κB and an association between the increased NF-κB expression and an increased level of IL-1β [23]. Thus, these results show the persistence of the effect of NF-κB on IL-1β [24,25].…”
Section: Discussionsupporting
confidence: 66%
“…NF-kB can stimulate the expression of cytokines such as TNF-a and IL-1b. These cytokines are resistant to NF-kB, further stimulate NF-kB and aggravate the occurrence of inflammatory reactions (Zhu et al, 2014). In 2006, Duman RS proposed the hypothesis of neurotrophic factors in depression, suggesting that BDNF can promote the growth of sudden contact and maintain the survival of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome NLRP3 is a component of innate immune system involved in the maturation of pro‐inflammatory cytokine IL‐1β. Scrophuloside B‐mediated inhibition of inflammasome NLRP3 expression via discussed pathway hinders IL‐1β secretion . Since these mentioned pro‐inflammatory mediators are critically involved in the pathophysiology of diabetic retinopathy, their inhibition may potentially prevent the progression of this complication.…”
Section: Chinese Herbs As Potential Antidiabetic Retinopathy Therapymentioning
confidence: 99%